Remote Substituent Effects on the Structures and Stabilities of PE π‑Stabilized Diphosphatetrylenes (R2P)2E (E = Ge, Sn) - Izod, Keith; Evans, Peter; Waddell, Paul G.; Probert, Michael R. (Inorganic chemistry, 2016)
A rare P–E π interaction between the lone pair of a planar P center and the vacant p orbital at the Ge or Sn center provides efficient stabilization for P-substituted tetrylenes (R2P)2E (E = Ge, Sn) and enables isolation of the first example of a compound with a crystallographically authenticated PSn bond. Subtle changes in the electronic properties of the bulky aryl substituents in these compounds change the preference for planar versus pyramidal P centers in the solid state; however, variable-temperature NMR spectroscopy indicates that in solution these species are subject to a dynamic equilibrium, which interconverts the planar and pyramidal P centers. Consistent with this, density functional theory studies suggest that there is only a small energy difference between the planar and pyramidal forms of these compounds and reveal a small singlet–triplet energy separation, suggesting potentially interesting reactivities.